PENGARUH STRATEGI BAURAN PEMASARAN RITEL TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN MINIMARKET MES MART SYARIAH - dheafani arnila pasaribu; Beby Karina Fawzeea Sembiring (Jurnal Media Informasi Manajemen, 2013)
AbstractThe goal of this research is to know and analize the effect of retail marketing mix strategy which consist of product, price, place, personality, and presentation on customer satisfaction of minimarket MES Mart syariah and to know and analize the effect of customer satisfaction on customer loyalty. This reseach is quantitative research. Population on this research is all of MES Mart Syariah’s customers in average 2.769 person per month. Sampling set method is using purposive sampling technic with criteria doing purchase transaction at least two times a month. Calculation of sampling is using Slovin formula so that obtained 100 samples.The theory used in this research is primary and secondary theory. The method of data collection is by fill the questionnaires with using Likert scale while the secontary data obtained by documentation study. The technic of analysis isdescriptive and quantitative analysis. First hypotesis test is using multiple linear regression analysis and the second hypotesis test is using simple linear regressionThe result of this research shows that simultaneously product, price, place, personality, and presentation have a positive and significant influences to customer satisfaction in MES Mart Syariah. Partial test shows that product, place, personality, and presentation have a positive and significant influence to customer satisfaction . while price in unsignificant effect with customer satisfaction. The result of this research also shows that customer satisfaction have a positive and significant influences to customer loyalty. From this research we can know that personality is the most dominant factor that effect to customer satisfaction.Key word : Retail marketing mix strategy, customer satistaction, loyalty